Influencia de la Sintomatología Prefrontal, Estrés Autopercibido y Consumo de Alcohol sobre las Quejas Subjetivas de Memoria en estudiantes universitarios - Chamba Calva, Wilmer Fernando (2018)
Abstract: The objective of this investigation was to analyze the relationship between subjective complaints of memory with prefrontal symptomatology, self-perceived stress and alcohol consumption in students from university. Memory Failures of Everyday (MFE-30), Prefrontal Symptomatology Inventory (ISP), Perceived Stress Scale (EEP) and Alcohol Use Disorders Identification Test (AUDIT) were administered to a sample of 253 from the socio-humanist area of Technical University of Loja, with an average of 21 years, which of them 68.73% were women. The results indicate that the relationship between subjective memory complaints with the other variables study is high and significant (r = 0.667; p < 0.001). It is important to mention that the prefrontal symptomatology is the variable that best predicts such complaints (β = 0.633, p < 0.001) and more specifically the attentional problems (β = 0.588, p < 0.001). It is recommended to continue this line of research in Latin America because these variables may become indicators of dementia or cognitive deterioration in early stages.